2008
DOI: 10.1303/aez.2008.227
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and its mode of action in different sedentary stages of Heterodera glycines (Tylenchida: Heteroderidae) by Verticillium lecanii hybrid strains

Abstract: The current study was conducted to investigate the pathogenicity and its mode of action by Verticillium lecanii hybrid strains in different sedentary stages of Heterodera glycines. Three different sedentary stages (pale yellow female, yellow brown cyst, and dark brown cyst) of H. glycines were treated with V. lecanii and incubated for 3 weeks on water agar. After 3 weeks of incubation, eggs were investigated for the following parameters: (i) the infection frequencies of eggs, (ii) the number of eggs laid, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Furthermore, this strain significantly reduced cyst and egg densities compared to the parental strains. Shinya et al (2008b) also evaluated the effects of fungal culture filtrates of the Lecanicillium hybrid strains on mature eggs, embryonated eggs (eggs fertilized but without development of juveniles), and J2 of SCN and compared these effects to those of their parental strains. The fungal culture filtrates of some hybrid strains inhibited egg hatch of mature eggs.…”
Section: Genetic Improvement Using Protoplast Fusionmentioning
confidence: 99%
“…Furthermore, this strain significantly reduced cyst and egg densities compared to the parental strains. Shinya et al (2008b) also evaluated the effects of fungal culture filtrates of the Lecanicillium hybrid strains on mature eggs, embryonated eggs (eggs fertilized but without development of juveniles), and J2 of SCN and compared these effects to those of their parental strains. The fungal culture filtrates of some hybrid strains inhibited egg hatch of mature eggs.…”
Section: Genetic Improvement Using Protoplast Fusionmentioning
confidence: 99%
“…The effectiveness of L. lecanii application caused by the conidia of the entomopathogenic fungus was able to infect variety of insect stages, starting from the egg, larvae and imago (Wang et al, 2007;Shinde et al, 2010;Park & Kim, 2010). The effication of L. lecanii also due to a wide range of hosts including the order; Homoptera, Hemiptera, Coleoptera, Lepidoptera; Orthoptera, nematodes and plant diseases (Gan et al, 2007;Goettel et al, 2008;Shinya et al, 2008). The advantages of L. lecanii was their ability to produce chitinase enzymes with high concentrations, these enzymes function as a degenerator of layers cuticle and toxic in killing host insects (Liu et al, 2003;Lu et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The evident of synergism between natural pesticides and entomopthogenic fungi L. lecanii was indicated as the increase in efficacy. It was found that the fungi and ASP, JSP acted as ovicidal on different insects species and nematodes (Shinya et al 2008a(Shinya et al & 2008b. Seed oil from both natural pesticides block natural micropyle that interfere on physiolocal process on egg development.…”
Section: Resultsmentioning
confidence: 99%